A Political Economy of Lebanon, 1948-2002 : The Limits of Laissez-faire - Gaspard, Toufic, (Social, Economic and Political Studies of the Middle East and Asia ;, 2004)
This book is about the laissez-faire strategy for economic development, a strategy inspired by neoclassical/mainstream economics, advocated by the "Washington Consensus", and implemented by the Bretton Woods institutions. Mainstream economics has taken legitimacy from the historical failure of command economies. But this view has not been balanced by an examination of the performance of laissez-faire economies, the closest to the pure market model. Lebanon provides a unique test case in this regard. The book assesses Lebanon's development during 1948-2002, including its industrial and financial performance. The dynamics of the laissez-faire system is separately studied from a Post-Keynesian perspective, highlighting institutional behavior. It is found that laissez-faire is not a sufficient condition for economic development, and can even be counterproductive.